Myristic acid is associated to low plasma HDL cholesterol levels in a Mediterranean population and increases HDL catabolism by enhancing HDL particles trapping to cell surface proteoglycans in a liver hepatoma cell model. (March 2016) - Noto, Davide; Fayer, Francesca; Cefalù, Angelo B.; Altieri, Ida; Palesano, Ornella; Spina, Rossella; Valenti, Vincenza; Pitrone, Maria; Pizzolanti, Giuseppe; Barbagallo, Carlo M.; Giordano, Carla; Averna, Maurizio R.
Abstract: Background: HDL-C plasma levels are modulated by dietary fatty acid (FA), but studies investigating dietary supplementation in FA gave contrasting results. Saturated FA increased HDL-C levels only in some studies. Mono-unsaturated FA exerted a slight effect while poly-unsaturated FA mostly increased plasma HDL-C. Aims: This study presents two aims: i) to investigate the relationship between HDL-C levels and plasma FA composition in a Sicilian population following a "Mediterranean diet", ii) to investigate if FA that resulted correlated with plasma HDL-C levels in the population study and/or very abundant in the plasma were able to affect HDL catabolism in an "in vitro" model of cultured hepatoma cells (HepG2). Results: plasma HDL-C levels in the population correlated negatively with myristic acid (C14:0, β = −0.24, p < 0.01), oleic acid (C18:1n9, β = −0.22, p < 0.01) and cis-11-Eicosenoic (C20:1n9, β = −0.19, p = 0.01) and positively with palmitoleic acid (C16:1, β = +0.19, p = 0.03). HepG2 cells were conditioned with FA before evaluating HDL binding kinetics, and only C14:0 increased HDL binding by a non-saturable pathway. After removal of heparan sulphate proteoglycans (HSPG) by heparinases HDL binding dropped by 29% only in C14:0 conditioned cells (p < 0.05). C14:0 showed also the highest internalization of HDL-derived cholesteryl esters (CE,  +32% p = 0.01 vs. non-conditioned cells). Conclusions: C14:0 was correlated with decreased plasma HDL-C levels in a Mediterranean population. C14:0 might reduce HDL-C levels by increasing HDL trapping to cell surface HSPG and CE stripping from bound HDL. Other mechanisms are to be investigated to explain the effects of other FA on HDL metabolism. Highlights: Plasma free fatty acids were correlated with HDL-C in a Sicilian population. Myristic acid resulted inversely correlated with HDL-C levels. Effects of fatty acids on HDL binding to hepatoma cells were evaluated "in vitro". Myristic acid increased HDL binding by increasing cells proteoglycan matrix.